Standardized simple mediation model : a numerical example - Fitrianto, Anwar; Midi, Habshah (IDOSI Publications, 2013)
Mediation models figure out how an effect occurred by hypothesizing a causal sequence. For a simple mediation model, a causal sequence is described in which an independent variable causes the mediator which sequentially causes the dependent variable. In this article, we tried to introduce to use standardized regression coefficient to the involving the simple mediation model since a standardized coefficient will be more meaningful than an unstandardized coefficients. In this article, we show that in simple mediation model, even though standardized regression coefficients are different from the unstandardized coefficients, but the standardized coefficients maintain the order of magnitude of the unstandardized regression coefficients for the simple mediation model.